Colonization and Collapse (2015)
ABSTRACT: Many species live in colonies that thrive for a while and then collapse. Upon collapse, very few individuals survive. The survivors start new colonies at other sites that thrive until they collapse, and so on. We introduce spatial and nonspatial stochastic processes for modeling such population dynamic. Besides testing whether dispersion helps survival in a model experiencing large fluctuations, we obtain conditions for the population to get extinct or to survive.